Fuzzy logic controller for vehicle-active suspension system - 431812 Tan, Wei Tek (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Electrical)) - Universiti Teknologi Malaysia, 2001